Conversion Of Blood Types And Identification Of Bacterial Species Causing Such Conversion - Susilo, Bagas; Junitha, I Ketut; Ramona, Yan (Metamorfosa: Journal of Biological Sciences; Vol 7 No 1 (2020)DO - 10.24843/metamorfosa.2020.v07.i01.p13, 2020)
Blood is one of the most important component of human body. In a case of crime, blood found at the site can be used as an evidence to track back the victim or the person who did such criminal. The main objective of this research were to investigate the time needed for the convertion of blood types and to identify bacterial species with capability to convert blood types. This research was conducted at Forensic Laboratory and Microbiology Laboratory, Faculty of Mathematics and Science, Udayana University. The methods used for detection of blood types and identification of Bacterias were elution method and vitex method, respectively. The results showed that blood type A on iron surface and ceramic media was changed into fake O type on day 25, while blood types of B and AB on ironic media were converted into fake type of O after 30 days of exposure. Two species bacteria ( Rhizobium radiobacter and Serratia ficaria ) with ability to convert blood type were identified in this research. Key Word : Rhizobium radiobacter, Serratia ficaria, changes of blood type s